Kongsberg Vision Meeting 2010 - Baraas, Rigmor C.; Einevoll, Gaute T. (Scandinavian Journal of Optometry and Visual Science, 2022)
Kongsberg Vision Meeting was arranged at Buskerud University College in Kongsberg for the third time on October 8, 2010. Rigmor C. Baraas and Gaute T. Einevoll organized the meeting. Keynote speakers were Joseph Carroll from the Medical College of Wisconsin, Milwaukee (USA) and Espen Hartveit from Department of Biomedicine, University of Bergen, Bergen (Norway).